THE ASSOCIATION OF HOMOCYSTEINE AND METHYLENE TETRAHYDROFOLATE REDUCTASE (MTHFR C677T) GENE POLYMORPHISM WITH DEEP VEIN THROMBOSIS IN THE POPULATION OF NORTH MACEDONIA - Brezovska-Kavrakova, Julijana Marko; Tosheska-Trajkovska, Katerina; Kostovska, Irena; Cekovska, Svetlana; Panov, Sasho; Petkovska, Lidija; Spasevski, Dejan (Journal of Morphological Sciences; Vol 3 No 1 (2020): JMS, 2020)
The implications of the methylene tetrahydrofolate reductase (MTHFR) gene and the level of total homocysteine (tHcy) in the pathogenesis of deep vein thrombosis (DVT) have been extensively studied in various ethnic groups. Our aim was to discover the association of MTHFR (C677T) polymorphism and homocysteine level in healthy subjects and in patients with DVT in the Republic of North Macedonia. The study group consisted of 123 healthy subjects, control group, and 93 consecutive ultrasonography and/or venography confirmed DVT patients. The concentration of plasma tHcy was determined by cyclical enzymatic method and the MTHFR gene polymorphism was analyzed by the polymerase chain reaction (PCR) and restriction fragment length polymorphism (RFLP).The results obtained for mean plasma tHcy in the control group were 9.7Â±3.65 Î¼mol/L, while tHcy level was significantly higher in patients with deep vein thrombosis - 15.19Â±3.63 Î¼mol/L (Ñ€<0.001). The highest frequency of mutation of MTFHR gene C677T was found for genotype CT, followed by wild genotype CC and the lowest frequency of genotype TT was found in control and DVT groups.The results have shown that plasma tHcy level is a contributing factor for development of this disease, DVT. Our findings have shown that MTHFR C677T polymorphisms were not associated with deep vein thrombosis in the selected population. Key words:total homocysteine,  deep vein thrombosis, methylenttetrahydrofolate reductase